f(x) = -2x² – 3 and g(x) = –2x-1 Find f(-4) and g(6) Simplify your answers as much as possible, Plz help

Question

f(x) = -2x² – 3 and
g(x) = –2x-1
Find f(-4) and g(6)
Simplify your answers as much as possible,

Plz help

in progress 0
Ngọc Hoa 1 year 2021-09-04T05:47:21+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-04T05:48:22+00:00

    Answer

    f(-4) = 125, g(6) = -13

    Step-by-step explanation:

    all of those symbols might look really scary, but really all the problem is asking you to do is substitute -4 into the x in f(x) and 6 into the x in g(x) — basically, f(-4) = [tex]-2((-4)^{3}) – 3[/tex] = 125, and g(6) = [tex]-2(6) – 1[/tex] = -13. there are your answers!

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )